A STUDY ON SOIL INVERTEBRATES IN DIFFERENT TERRESTRIAL ECOSYSTEMS OF SIMILIPAL BIOSPHERE RESERVE, MAYURBHANJ, ORISSA - M. K. LENKA,; N. MOHANTY,; B. C. GURU,; S. GIRI, (The Bioscan, 2010)
Density and biomass of certain soil invertebrates were studied in different ecosystems of Similipal Biosphere Reserve. The density of soil invertebrates like ants, termites, arachnida, myriapoda, nematodes, earthworms and larvae was significantly different (ANOVA) among cropland, fallowland and forest ecosystems. Although the biomass of all these invertebrates was higher in forest ecosystem, it was not statistically significant among these three types of systems. Ant, termite and myriapoda were absent in cropland whereas arachnida and myriapoda were absent in fallowland.